2010
DOI: 10.1186/1471-2105-11-367
|View full text |Cite
|
Sign up to set email alerts
|

A flexible R package for nonnegative matrix factorization

Abstract: BackgroundNonnegative Matrix Factorization (NMF) is an unsupervised learning technique that has been applied successfully in several fields, including signal processing, face recognition and text mining. Recent applications of NMF in bioinformatics have demonstrated its ability to extract meaningful information from high-dimensional data such as gene expression microarrays. Developments in NMF theory and applications have resulted in a variety of algorithms and methods. However, most NMF implementations have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
1,037
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,163 publications
(1,090 citation statements)
references
References 26 publications
4
1,037
0
Order By: Relevance
“…We have shown that by using non-negative matrix factorization, the superburst spectra of 4U 1636-536 can be decomposed into two variable spectral components: the cooling burst spectrum, and a boundary/spreading layer, which is found to be contributing a sizable fraction of the total luminosity during the superburst. The spectral properties of the boundary/spreading layer component favors the spreading layer model (Inogamov & Sunyaev 1999, 2010Suleimanov & Poutanen 2006), where the spectrum is a constant ∼2.5 keV, quasi-Planckian component varying just in normalization as the burst evolves. This component is also very reminiscent of the frequency-resolved spectral component of a constant spectral shape that is responsible for the sub-second variability in many NSLMXBs.…”
Section: Spectral Fittingmentioning
confidence: 93%
See 2 more Smart Citations
“…We have shown that by using non-negative matrix factorization, the superburst spectra of 4U 1636-536 can be decomposed into two variable spectral components: the cooling burst spectrum, and a boundary/spreading layer, which is found to be contributing a sizable fraction of the total luminosity during the superburst. The spectral properties of the boundary/spreading layer component favors the spreading layer model (Inogamov & Sunyaev 1999, 2010Suleimanov & Poutanen 2006), where the spectrum is a constant ∼2.5 keV, quasi-Planckian component varying just in normalization as the burst evolves. This component is also very reminiscent of the frequency-resolved spectral component of a constant spectral shape that is responsible for the sub-second variability in many NSLMXBs.…”
Section: Spectral Fittingmentioning
confidence: 93%
“…For calculating the decomposition we used the package nmf (Gaujoux & Seoighe 2010) that calculates the standard NMF (Brunet et al 2004) by picking random starting values for W and S from a uniform distribution [0,max(X)] and then updating iteratively 10000 times to find a local minimum of the cost function with a multiplicative rule from Lee & Seung (2001). The minimization process is repeated for 300 starting points to ensure that the algorithm does not get stuck in a local minimum.…”
Section: Spectral Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heatmaps visualizing the hierarchical clustering of immunoglobulin profiles were established using the hclust-R function with default parameters and plotted using the heatmap function from the NMF R package [14].…”
Section: Hierarchical Clusteringmentioning
confidence: 99%
“…The NMF package (Gaujoux and Seoighe 2010) picks random starting values for W and H and then updates iteratively to find a local minimum of KL divergence. We repeated this process for 100 different starting points for each value of k, and used the results to evaluate the quality and stability of the factorization at this degree.…”
Section: Non-negative Matrix Factorizationmentioning
confidence: 99%